Use of state lands allocated to middle class families for cultivation: A case study of Pitabeddara DS Division in Matara District. - Gunawardana, N.A. (University of Colombo, 2015)
Land Development Ordinance (LDO) can be cited as the basis for policy.The set of rules as to how the alienation of land , is incorporated in the LDO.The present situation of land resource management background is that there is a total land area of 6,552,500 hectares covering a population of about 20 million. When considering the cultivation in the country 35 percent is of agriculture usage,31 percent is under forest and 34 percent is under tea cultivation,patana grass, pasture and urban uses. (Food and Agriculture Organization of the United Nations,Rome 1989) During the period from 1936-66, 1264 thousand acres were released for agricultural purposes.During this period 147 thousand acres of land was alienated for middle class allottes.Then after a certain time period the middle class alienation was dropped by the Government according to the land utilization committee report of 1967. This project was dropped as the expected objectives were not reached by the Government. (Report of the Land Utilization Committee,August 1967.SP.11) The allocation of Middle Class (MC) allotments are designated at Land Kachcheries,selected applicants receive the permits for the occupation and they are required to make an annual payment to retain the permit. Once the land is developed the holder is eligible to receive a Grant which is issued after the land has been completely surveyed.The Grant has many characteristics of a property title but the land is still considered as a state land,because the grant holder cannot transfer the title or lease or mortagage the land without the approval of the Land Commissioner
Keywords: Use of state lands allocated to middle class families for cultivation: A case study of Pitabeddara DS Division in Matara District